Effect of Weed Competition, Planting Time and Depth on Pistacia atlantica Seedlings in a Mediterranean Nursery in Iran - Hosseini,Seyed Mohsen (2007)
The effect of weed competition, Planting time and Depth on growth and survival of Pistacia atlantica seedlings was evaluated in nursery conditions. Pistacia atlantica is a deciduous tree species that belongs to the Anacardiaceae family. It is valuable for soil conservation and therefore suitable for plantation in dry lands. Regeneration of Pistacia atlantica in western part of Iran presents problems due to much destruction of its natural habitats. Two levels of weed treatment (weed competition was removed several times by hand or the weeds permitted to grow) and three levels of sowing date (9 January, 29 January, 18 February) were used. In addition, seeds were sown at three different depths (0.4 and 8 cm) but no seedlings emerged when seeds were sown at 0 cm sowing depth. At the end of the first growing season on September 2004, survival, height above the soil surface, collar diameter, shoot/root length ratio and shoot/root dry weight ratio were measured. Survival was significantly affected by sowing depth but not by sowing date and weed treatment. Survival was greater at 4 cm than at 8 cm sowing depth. Collar diameter was significantly greater at 4 cm than at 8 cm sowing depth and in 9 January and 29 January than in 18 February sowing date but was not different between weed treatments. Shoot/root length ratio and height was not affected by sowing date, sowing depth and weed treatment. Shoot/root dry weight ratio was significantly lower at 4 cm sowing depth but not affected by sowing date. This ratio was greater in weed competition condition. In general weed treatment, sowing date and sowing depth are factors that can influence physical and morphological traits of seedlings.